Natural capital and human capital : three essays in Sub-Saharan Africa - (:unkn) unknown (My University, 2024)
This thesis aims to analyse the impact of natural capital on human capital. It focuses on Sub-Saharan African (SSA) countries that are heavily exposed to environmental degradation. Overall, the results of the thesis corroborate that natural capital degradation, such as air pollution and the loss of forest cover, affects human capital and, more specifically, the health of individuals in sub-Saharan Africa. The thesis is divided into three original chapters. Chapter 1 examines the relationship between the presence of a protected area and the choice of cooking fuel in Côte d'Ivoire. Environmental objectives, namely reducing forest and biodiversity losses, lead to the implementation of protected areas. However, preserving the environment could also change the choice of cooking fuels made by households living near protected areas. Using data from the 2015 Household Living Standards Survey and a multilevel mixed effects model show that a protected area increases the probability of using purchased biomass (firewood or charcoal) compared with clean energy (gas). The effect depends on the characteristics of the household head, the household's socio-economic status, the level of development of the area of residence and the level of protection of the protected area. Thus, integral protected areas increase the probability of using clean energy. Besides shedding light on the determinants of fuel choice, this chapter provides a better understanding of the consequences of establishing protected areas. Indoor air pollution is a public health problem in developing countries, especially in sub-Saharan Africa, where households mostly rely on solid fuels to cover their energy needs. Women, who are usually responsible for cooking, and their young children are the most exposed to indoor air pollution. Chapter 2 analyses the causal relationship between indoor air quality and the risk of respiratory diseases in individuals in Côte d'Ivoire, according to age group. By creati
Keywords: African Research